2013
DOI: 10.1021/ie401568x
|View full text |Cite
|
Sign up to set email alerts
|

Coal Chemical Looping Gasification for Syngas Generation Using an Iron-Based Oxygen Carrier

Abstract: The chemical-looping gasification (CLG) of coal is a clean and effective technology for syngas generation. Sharing principles with chemical-looping combustion (CLC), CLG also uses oxygen carriers to transfer lattice oxygen to the fuel. Investigations into CLG with different O/C ratios are carried out in a fluidized bed reactor with steam used as the gasification− fluidization medium. The effect of the active component content of the oxygen carrier on the gas selectivity is performed, and reaction mechanisms be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 134 publications
(67 citation statements)
references
References 23 publications
1
63
1
2
Order By: Relevance
“…In addition to coal gasification [10,11] and natural gas oxidation [12][13][14], syngas can be efficiently manufactured from renewable dry biomass [15,16]. The catalytic synthesis of ethanol and higher alcohols from syngas is a reliable method of energy and fuel production independent of fossil resources.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to coal gasification [10,11] and natural gas oxidation [12][13][14], syngas can be efficiently manufactured from renewable dry biomass [15,16]. The catalytic synthesis of ethanol and higher alcohols from syngas is a reliable method of energy and fuel production independent of fossil resources.…”
Section: Introductionmentioning
confidence: 99%
“…One way is to mechanically add NiO [13] or CaO [7,14,15] into the Fe-based oxygen carrier. These mixtures as oxygen carrier created a synergistic effect on enhancing the fuel conversion due to the inevitable contact among char, catalysts and oxygen carrier.…”
Section: Introductionmentioning
confidence: 99%
“…CLG involves a high degree of coupling that integrates catalytic coal gasification with chemical-looping technology. In contrast to traditional coal gasification technologies, CLG has several advantages [2,3]. First, the use of oxygen carriers as catalysts for gasification reactions allows for lower reaction temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As inexpensive oxygen carriers, Mn-based and Fe-based oxygen carriers are also environmentally friendly. However, both of these oxygen carriers have several inherent disadvantages for CLG, such as a low oxygen-carrying capacity for Fe-based oxygen carriers [2] and low reactivity for Mnbased oxygen carriers [6]. A previous study of a Cu-based oxygen carrier [8] revealed that it has high reactivity and oxygen-carrying capacity but that its applications are limited by its low melting point and tendency to agglomerate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation